Use of remotely piloted aircraft systems in monitoring pest and diseases in agricultural crops: global literature review - Eugenio, Fernando Coelho; Soares, Filipe Rocha Louzada; Silva, Jaine Honorato Oliveira da; Ruoso, Régis; Fantinel, Roberta Aparecida (Acta Scientiarum. Technology, 2023)
The use of Remotely Piloted Aircraft Systems (RPAS) as Remote Sensing platforms has been gaining more and more applicability in various fields of study, one of them being the agricultural sector. The interest in this technology segment is mainly due to its flexibility to acquire high-resolution data quickly. Data that helps, for example, identify and monitor pests and diseases. Therefore, this work aims to develop a systematic analysis at a global level to assess the evolution of publications over the years and the current state of the art in the use of RPAS technology in monitoring pests and diseases in crops. Twenty-nine scientific articles came from the Web of Science, Scopus, and Google Scholar platforms, identifying the places of origin of publications, agricultural species, platforms, and sensors. China and the United States published most of the works. Multirotor platforms have been more used compared to fixed-wing platforms. RGB (Red, Green, and Blue) and Multispectral sensors totaled 25% and 40.44%, respectively. It is expected that technological advances and RPAS improvement increasingly strengthened the control of pests and diseases in crops, contributing to a greater appreciation of the benefits of this system.